The sugar beet industry - Gillis, Fred Norton (My University, 1903)
Introduction: It is very difficult to trace the exact origin of the sugar beet, but its cultivation has been known to have taken place in very remote periods of time. Even so far back as the latter part of the fifteenth century two varieties were spoken of, the red and the white. Oliver de Serres, in his writings in 1590 only mentions the red beet and states that it had not been introduced into Europe. He also said that the juice that this beet yielded on boiling is similar to sugar syrup. The red variety vas introduced into England about 1548 while the white variety was first introduced in 1590. A small variety known as "Diseete" which is still grown for feed, to a considerable extent in France, was believed to have originated in Germany. Up to this date the root was not thought to have any industrial value, but was cultivated only for the table or for cattle food. In 1747 Margraff believing sugar to be regular constituent of plants other than cane, made an examination of different vegetables and succeeded in separating from several varieties, varying amounts of crystallizable sugar. His method was to cut the vegetable into thin slices, rapidly drying it, reducing it to a fine powder and then exhausting it with dilute alcohol. Of all these vegetables beets were round to contain the largest amount of sugar and although he advocated the growing of beet for production as a great commercial product of Europe, yet he was not destined to see the fulfillment of his plans, as his methods were at best very crude and the prices of Colonial sugar were so low as to render competition impracticable. On account of these drawbacks the great industry which Margraff had discovered lay dormant for a half a century when the work was taken up by one of his pupils who after a considerable amount of work succeeded in extracting sugar from the beets on a large scale. The methods used were entirely his own and they gave astonishing results. He announced these results in 1797, publishing his mode of operation and in the latter part of 1799 presented a sample of his product with a description of his method to the Institute of France, stating that the cost of production need not exceed six cents a pound.
Citation: Gillis, Fred Norton. The sugar beet industry. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Sugar Beets; Agriculture; Sugar Production; Theses